Satisfacción al usuario en el gobierno autónomo descentralizado municipal del cantón Vinces. - Cruz Moreno, Joel Sebastián (2022)
The Municipal Decentralized Autonomous Government of the Vinces Canton is a public company, dedicated to providing services to its users who live in said canton, it is located between Sucre and 9 de Octubre streets, it is currently directed by the Mayor Alfonso Montalvan Cerezo. The present case study whose objective is to make known how efficient the staff that works in the Municipal GAD of Vinces is and to analyze how is the quality of the service offered by the company to the users, the research method that was used was the descriptive method, which allowed knowing and collecting effective information through interviews and surveys that were carried out on the mayor of Vinces and the users who carry out procedures or any other activity in the Municipal GAD, respectively. It is common knowledge that in recent years the pandemic caused a significant impact on people and much more on companies because we were not prepared for something of great magnitude and this is where most of the problems arose in the Municipal GAD of the Vinces Canton. Through the collection and tabulation of information, it was possible to show that user satisfaction is regular, this means that the company must improve so that it provides satisfaction to users efficiently and effectively.